Exercise Program in Post-Surgical Release of Knee Flexion Contracture in Patient with Osteochondroma: A Case Report: A Case Report - Deva Natalia Motik; Ida Kurniawati (Physical Therapy Journal of Indonesia, 2021)
Introduction: Knee flexion contracture is caused by adaptive shortening of the muscles which is marked by the incapability of the knee to fully extend. This condition is associated with long periods of immobilization, pain, and muscle weakness that are caused by various pathological conditions. Post-surgical rehabilitation program is mainly aimed to recover basic lower limb functions through an exercise program. Case description: A 16-year-old male patient with a history of left-sided knee pain and fixed flexion contracture was undergone a surgical release procedure and diagnosed with osteochondroma. Post-surgical evaluation by physical therapist found muscle atrophy, limited range of motion, and pain on the operated limb. The patient was instructed to do muscle strengthening and active exercise on both legs. Exercise program post-surgery aimed to improve muscle strength, range of motion, functional limb ability and activities of daily living. Improvement in the range of motion of the left knee joint was observed after three sessions of physical therapy intervention. Conclusion: Exercise program could reduce the muscle contracture and improve the knee joint range of motion in patients with osteochondroma following surgical release procedure.